Development and Validation of the Turkish Version of the Colorectal Anal Distress Scale-8 - Serdar AYDIN; Tuğçe İrem PAŞA; Merve BIDAK; Gonca BATMAZ; Ramazan DANSUK (Bezmiâlem Science, 2017)

(untitled)
Objective:Pelvic floor disorders are common and include a wide spectrum of conditions such as pelvic organ prolapse, urinary incontinence, fecal incontinence, voiding and/or defecation dysfunction, sexual dysfunction, and several chronic pain syndromes. There is a need for a validated and reliable inventory to evaluate colorectal anal distress in women with pelvic floor disorders. The aim of this study was to investigate the reliability and validity of the Turkish version of the CRADI-8 for the evaluation of colorectal distress.Methods:Overall, 101 women, some with pelvic floor disorders, were enrolled in the study. The Turkish version of the CRADI-8 was developed using forward back translation. Cronbach’s alpha was used to assess the internal consistency of the Turkish version. Receiver operating characteristic (ROC) analysis was performed to determine the optimal cutoff values for determining the presence of colorectal distress. The discriminant validity was assessed by comparing the mean scores of the rectocele and control groups. Correlation analysis was examined for convergent validity.Results:The Cronbach’s alpha value was 0.763. A Spearman correlation coefficient of r=0.823 was found between the POP-Q score and the inventory score (p<0.0001). The correlation coefficient of the rectocele stage and CRADI-8 score was calculated to be r=0.924 (p<0.0001). The one-factor unidimensional model explained 79.3% of the total variance. Discriminant ROC analysis of the Turkish version of the CRADI-8 demonstrated that the AUC for the total FSDS-R score was 0.76 (0.64–0.88) at the baseline, confirming the moderate discriminant validity of the scale.Conclusion:The Turkish CRADI-8 is a valid, reliable tool for the evaluation of colorectal anal distress and symptoms in women with posterior vaginal wall defects and pelvic floor dysfunction.